2020
DOI: 10.12783/dtetr/amee2019/33430
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Vacuum Adsorption Wall Climbing Robot

Abstract: In this paper, a new type of wall climbing robot with multi vacuum suckers is developed. The robot structure and working principle are introduced in detail. The analysis of safe adsorption force of the wall climbing robot. The mechanical model of the suckers is established. The adsorption force of the suckers is determined based on the experiments. The robot prototype is made. And a large number of experiments are carried out to verify the feasibility of the wall climbing robot. The experiments include robot w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Its crossing obstacle ability is up to 10 cm, which is better than the latest wall-cleaning robot. [1][2][3][4][5][6][7][8][9][10] When the robot is lifted to fly over the obstacle, the effect is shown in Figure 18(a), where the white foam bar is the simulated obstacle. The cleaning effect of common glass stains is also experimented in this article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its crossing obstacle ability is up to 10 cm, which is better than the latest wall-cleaning robot. [1][2][3][4][5][6][7][8][9][10] When the robot is lifted to fly over the obstacle, the effect is shown in Figure 18(a), where the white foam bar is the simulated obstacle. The cleaning effect of common glass stains is also experimented in this article.…”
Section: Resultsmentioning
confidence: 99%
“…It contains key technologies with facade adsorption, designs of lifting device, and related control methods. Facade adsorption technologies for glass curtain walls include the passive sucker, [1][2][3] the active sucker, 4,5 the thrust adsorption by using fans, [6][7][8][9] and so on. Lifting technologies include rope driven, 6,8,9 leg types, 4 wheel types, 3,7 and sliding frame types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al suggested a new form of multi-vacuum sucker wall climbing robot. The robot can walk vertically on a variety of materials [9]. Yu et al developed a new legged gecko robot with 16 active degrees of freedom and 12 passive degrees of freedom that could climb omni-directional surfaces with dry adhesive material using a diagonal gait motion.…”
Section: Introductionmentioning
confidence: 99%